Effect of Work-Life Balance and Welfare Level on Millennial Employee Performance Through Work Engagement - Agis Sa’adah Puspitasari; Muhammad Darwin (GoAcademica Research & Publishing, 2021)
Industrial Revolution 4.0 is a phenomenon that collaborates with cyber technology and automation technology. this research aims to conduct scientific research on the role of work-life balance and the level of welfare of millennial employees through work engagement as a variable intervening. The participation of respondents to this study is the general of millennials who has worked in the Jakarta area, aged 21-36 years. Researchers used the purposive sampling method. This study uses a work-life balance measurement tool with a balance dimension in time management, engagement balance, balance in expectation fulfillment, and satisfaction balance. Besides, at the level of well-being with meaningful work-life factors, good social relationships, work attachment, self-actualization, comfortable circumstances, self-acceptance. While employee performance is measured through the work environment, ability to do work, and motivation. Work Engagement is measured by vigor, dedication, and absorption indicators. The analysis technique used is Structural Equation Modeling based on VB-SEM using SmartPLS software. The results showed that five hypotheses of direct influence were accepted and one rejected. While the two hypotheses of indirect influence are each rejected and accepted. Work Engagement variables as intervening variables are only capable of mediating Work-Life Balance against Employee Performance.